Analysis of Pedestrian Performance by Integrating both Quantitative and Qualitative Factors - Neil Andrew I. Meneses; Jocelyn S. Buluran (Civil Engineering Journal, 2022)
The importance of non-motorized movements, explicitly walking, and its corresponding impact on social, economic, and environmental aspects has always been overlooked due to the convenience brought by motorized vehicles. An automobile-dependent society mirrors the rise and worsening of several transportation problems, such as road-wide traffic congestion, massive fuel consumption, and excessive CO2emissions. In response to these aggravating situations and in support of various national and international calls, the main objective of this study was to extract the significant factors influencing the pedestrian level of service and walkability and to subsequently develop a predictive mathematical model for evaluating pedestrian conditions. Factors influencing the pedestrian level of service and walkability were initially identified through an extensive review and evaluation of existing studies, literature, and other relevant resources. A cause-and-effect analysis was used to develop an Ishikawa Diagram tackling pedestrian performance. The finalized factors were incorporated into the development of the Pedestrian Performance Assessment Questionnaire (PPAQ), which was utilized for data acquisition. Survey responses were then subjected to factor analysis after satisfying several tests for assumptions and suitability to extract the root causes influencing pedestrian performance. The validated root causes were then integrated to form the Pedestrian Performance Audit Tool (PPAT), a tool used in evaluating pedestrian areas in Tarlac City, Philippines. Data was analyzed through ordinal regression analysis to develop the multi-objective pedestrian performance prediction model. Results showed that there are six critical predictors of pedestrian performance unified in the final mathematical model: Pedestrian Space (PS), Official’s Intervention (OI), Ambiance (A), Vibrance (V), Street Vendors (SV), and Trash Bins (TB), and is the most significant contribution of the study. The model's validity was ascertained through a confusion matrix, which resulted in an acceptable rating. The comparison between calculated and perceived values together with the use of odds ratios served as the basis for the interpretation of some of the key results and findings. Finally, recommendations were also presented which can be a basis for the development of sustainable programs and interventions for the improvement of the pedestrian system. Doi: 10.28991/CEJ-2022-08-06-02 Full Text: PDF